Ripeness Levels and Their Relations with the Success of the Negotiation Method: CPP-NPA, TTP, IRA - Emrah KAYA (Gazi Akademik Bakış)
Conflict arises for a variety of reasons. Parties may fail to achieve clear success in the conflict process and achieve their goals. In such a situation, conflict causes the parties to reach the mutually hurting stalemate. The realization of this situation by the parties signifies the ripening of the conflict. In a ripening conflict, alternative methods come to the fore. At this point, one of the preferred tools is the negotiation method. A similar process takes place in low-intensity conflicts between states and terrorist organizations. After prolonged conflicts, contacts between the parties occur and thus negotiations are initiated. However, the negotiation method isn’t always end with successful, and it is possible to return to the conflict environment at different phases of the negotiation. This study argues that there are different levels of ripeness. At the same time, it is evaluated that there is a significant relationship between the levels of ripeness and the probability of success of the negotiation method.